Marketing essentials - Farese, Lois Schneider; Kimbrell, Grady; Woloszyk, Carl A. (New York : Glencoe / Mc Graw-Hill, 1997)
Business
2004-11-23
Keywords: Marketing; Basic marketing; Domestic marketplace; Global marketplace; Selling; Sales proces; Retail sales; Advertising media